Activation of a Bis‐(Phenoxyimine) Titanium (IV) Catalyst Using Different Aluminoxane Co‐Catalysts. Issue 1 (15th October 2015) - Romano, Dario; Ronca, Sara; Rastogi, Sanjay; Soares, João B. P.
Summary The activation of a bis‐phenoxyimine catalyst based on titanium (IV) using different aluminoxanes (MAO, PMAO and MMAO12) has been studied. The effect of a co‐catalyst modifier (BHT) used in combination with the MAO has been also tested. In particular, the effect of the activation time between the catalyst and the different aluminoxanes has been taken into consideration. On increasing the activation time between catalyst and the different aluminoxanes and TMA‐free MAO, differences in the catalyst activities have been observed. UHMWPEs having a reduced number of entanglements have been synthesized activating the FI catalyst with MAO and TMA‐free MAO. The obtained reactor powders can be solid‐state processed below the melting temperature in order to obtain high modulus/high tenacity tapes used for body armor and vehicle protection applications.